The self-assessment of quality culture and dimensions of social responsibility on the example of Pomeranian public organizations - winners of the Pomeranian Quality Award - Wiśniewska, Małgorzata Zdzisława (Zielona Góra: Faculty of Economics and Management Press)
The research problem is as follows: What is the level of quality culture in public organizations participating in the competition for the Pomeranian Quality Award? The purpose of the study is to identify the level of quality culture in selected public organizations and identify the strengths and weaknesses of the quality culture of these organizations. A self-assessment, desk research, expert evaluation, and the method of synthesis and logical inference were used as research methods.
Keywords: quality; organizational culture; social responsibility; excellence models; Pomeranian Quality Award